Cultural adaptation and validation of the "Kidney Disease and Quality of Life - Short Form (KDQOL-SF™ 1.3)" in Brazil - Duarte,P.S. (2005)
The objective of the present study was to translate the Kidney Disease Quality of Life - Short Form (KDQOL-SF™1.3) questionnaire into Portuguese to adapt it culturally and validate it for the Brazilian population. The KDQOL-SF was translated into Portuguese and back-translated twice into English. Patient difficulties in understanding the questionnaire were evaluated by a panel of experts and solved. Measurement properties such as reliability and validity were determined by applying the questionnaire to 94 end-stage renal disease patients on chronic dialysis. The Nottingham Health Profile Questionnaire, the Karnofsky Performance Scale and the Kidney Disease Questionnaire were administered to test validity. Some activities included in the original instrument were considered to be incompatible with the activities usually performed by the Brazilian population and were replaced. The mean scores for the 19 components of the KDQOL-SF questionnaire in Portuguese ranged from 22 to 91. The components "Social support" and "Dialysis staff encouragement" had the highest scores (86.7 and 90.8, respectively). The test-retest reliability and the inter-observer reliability of the instrument were evaluated by the intraclass correlation coefficient. The coefficients for both reliability tests were statistically significant for all scales of the KDQOL-SF (P < 0.001), ranging from 0.492 to 0.936 for test-retest reliability and from 0.337 to 0.994 for inter-observer reliability. The Cronbach's alpha coefficient was higher than 0.80 for most of components. The Portuguese version of the KDQOL-SF questionnaire proved to be valid and reliable for the evaluation of quality of life of Brazilian patients with end-stage renal disease on chronic dialysis.